Strategi Pengumpulan Zakat dalam Hadis Nabi: Pendekatan Tematik: Zakat Collection Strategy in the Hadith of the Prophet: A Thematic Approach - Azwar, Azwar; Arifuddin Ahmad; Siti Aisyah Kara (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to explore and map the strategies employed by the Prophet Muhammad (peace be upon him) in the collection of zakat, based on a thematic analysis of Hadiths (mawḍūʿī), with the hope of identifying normative and practical values applicable to contemporary zakat systems. Employing a qualitative method and a thematic Hadith approach, the findings reveal that the Prophet’s strategies emphasized the moral integrity of zakat officers, strict regulation, legal enforcement, and efficient management. Zakat officers were not only tasked with administrative duties but also bore significant moral responsibilities to uphold trust and public confidence. The implications of these findings highlight the urgency of strengthening the integrity of zakat personnel, the necessity of rigorous oversight and transparency in management, the enforcement of clear regulations, and the adoption of modern managerial and technological systems to enhance the efficiency of zakat collection and distribution. These aspects form a crucial foundation for contemporary zakat institutions to ensure sustainability and maintain public trust. The recommendations proposed include ethical and social responsibility training for zakat officers, the development of transparent auditing and supervisory systems, the implementation of firm regulations with clearly defined sanctions, the optimization of digital technologies for zakat management, and ongoing public education on the role of zakat in promoting social justice and alleviating poverty.